Engineering In‐Plane Nickel Phosphide Heterointerfaces with Interfacial sp HP Hybridization for Highly Efficient and Durable Hydrogen Evolution at 2 A cm−2. Issue 4 (25th November 2021) - Zhou, Qian; Liao, Liling; Bian, Qihang; Yu, Fang; Li, Dongyang; Zeng, Jinsong; Zhang, Long; Wang, Hui; Tang, Dongsheng; Zhou, Haiqing; Ren, Zhifeng
Abstract: The catalytic hydrogen‐evolving activities of transition‐metal phosphides are greatly related to the phosphorus content, but the physical origin of performance enhancement remains ambiguous, and tuning the catalytic activity of nickel phosphides (NiP2 /Ni5 P4 ) remains challenging due to unfavorable H* adsorption. Here, a strategy is introduced to integrate P‐rich NiP2 and P‐poor Ni5 P4 into in‐plane heterostructures by anion substitution, in which P atoms at the in‐plane interfaces perform as active sites to adsorb H* and thus facilitate the hydrogen evolution reaction (HER) process via modulating the electronic structure between NiP2 and Ni5 P4 . Consequently, the NiP2 /Ni5 P4 hybrid exhibits an outstanding hydrogen‐evolving activity, requiring only 30 and 76 mV to afford 10 and 100 mA cm −2 in acid, respectively. It surpasses most of the earth‐abundant electrocatalysts thus far, and is comparable to Pt catalysts (30/72 mV at 10/100 mA cm −2 ). Particularly, it can run smoothly at large current density and only requires 247 mV to reach 2000 mA cm −2 . Detailed theoretical calculations reveal that its exceptional activity stems from the moderate overlap of density states between P 2p and H 1s orbitals, thus optimizing the H*‐adsorption strength. This work highlights a new avenue toward the fabrication of robust non‐noble electrocatalysts by constructing in‐plane heterojunctions. Abstract : An in‐plane heterostructure engineering strategy is employed to optimize the catalytic hydrogen‐evolving activity of nickel phosphides (NiP2 /Ni5 P4 ) by tailoring the local electronic structure of P atoms at the interfaces. The resultant NiP2 /Ni5 P4 heterostructures deliver Pt‐like activity, requiring extremely low overpotentials of 30 and 76 mV to achieve current densities of 10 and 100 mA cm −2 in acidic electrolytes, respectively.